Evaluation of potential toxicity of Steriplant©N aerosolization toward human alveolar cells A459 in vitro. (September 2021) - Pintarič, Robert; Matela, Jože; Pintarič, Štefan; Novak, Matjaž; Filipič, Metka
Protection of patients against hospital-acquired infections is of major importance. Disinfection of magnetic resonance imaging suites is, due to their unique properties and environment particularly, difficult to implement. We developed an OPTI-JET CS MD 2ZE aerosolizator for disinfection of a magnetic resonance imaging suite using the electrolyzed oxidizing water biocide Steriplant © N. The disinfection of the magnetic resonance imaging suite with this system reduced from the number of colony formed unit/m 3 air by 87% and 96% in 6 and 15 min of disinfection, respectively. It is well known that exposure of personnel or patients to aerosols may represent risk to the respiratory system; therefore, the aim of this study was to assess potential cytotoxicity and genotoxicity of Steriplant © N aerosolization toward human alveolar cells A459 in vitro . The A459 cells were exposed to aerosol containing different concentrations (50% and 100% v/v) of Steripalnt © N for 6 min in a chamber that had been constructed to simulate the conditions in the magnetic resonance imaging suite. The cytotoxicity was evaluated by measuring iodide uptake, and the genotoxicity was determined by measuring formation of phosphorylated H2AX histones, a marker for deoxyribonucleic acid double-strand breaks, immediately after the aerosolization and after 1, 4, and 24 h postincubation. The results demonstrated that aerosolization with Steriplant © N at conditions reflecting aerosolization in a magnetic resonance imaging suite is not cytotoxic and does not exhibit genotoxic potential in vitro.